Pediatric Mixed Functioning Adrenocortical Carcinoma: A Case Report and Review of Literature - Sanjay Yadav; Chandan Jha; Saroj Mishra; Ritu Verma; Abhishek Krishna (Middle East Journal of Cancer, 2019)
Adrenocortical carcinoma (ACC) is a very rare disease in the pediatric age group. The clinic-biological profile, histopathological criteria of diagnosis, and staging of this disease in this age group are different from those of adult ACC. In this paper, we report a case of pediatric ACC presenting as Cushing syndrome that was managed with complete surgical excision. Through this case presentation, we highlight the sequential protocol of investigations and management in a child suspected of having ACC.